The subsequent risk of retinal vein occlusion disease after sinusitis diagnosis: a nationwide population-based study - Tsan-Yu Tsai; Jing-Yang Huang; Shih-Chun Chao; Shuo-Min Hsu; Shun-Fa Yang; Hung-Yu Lin (Scientific Reports, 2024)
Abstract Retinal vein occlusion (RVO) is a common retinal vascular disease that causes visual impairment. However, there is limited evidence regarding the relationship between sinusitis and risk of RVO. This study investigated the association between sinusitis and the subsequent risk of RVO disease. A retrospective cohort study was conducted and patients with sinusitis or RVO were selected from the National Health Insurance Research Database (NHIRD) of Taiwan. In this population-based study, we identified a total of 131,532 sinusitis patients, who were matched with 263,064 non-sinusitis individuals based on sex and age. The Cox proportional hazard regression was applied to demonstrate the adjusted hazard ratio (aHR) with 95% confidence interval (CI) of main outcomes. Our results showed that the crude hazard ratio (cHR) for the risk of RVO was 1.35 (95% CI: 1.20–1.52) in the sinusitis cohort compared with the non-sinusitis cohort. After adjustment for demographics and comorbidities in the multivariable cox regression, the adjusted hazard ratio (aHR) was 1.28 (95% CI: 1.13–1.44). Moreover, statistically significant differences were observed in the 14-year cumulative incidence of RVO (p < 0.0001), central RVO (p = 0.0002), and branch RVO (p = 0.0004) between the sinusitis and non-sinusitis cohorts. In conclusion, our study revealed that patients with sinusitis were at higher risk of being diagnosed with RVO.